Analisis Semiotika Body Shaming Dalam Film Imperfect Perspektif Roland Barthes - Arina Putri Hasanah Marpaung; Achiriah (STAI Bumi Silampari, 2025)
This study aims to analyze the representation of bodyshaming in the film Imperfect using Roland Barthes' semiotic approach. The main focus is to identify symbols and signs that portray social pressure on women's bodies through both visual and verbal narratives in the film. The research employs a qualitative descriptive method, with data collected through direct observation of the film and documentation of relevant scenes. The findings reveal that symbols such as scales, mirrors, clothing, and character interactions carry strong connotative meanings that shape societal perceptions of beauty standards. The film effectively illustrates how bodyshaming impacts the main character’s identity, self-esteem, and social relationships. However, an ambiguity in the message arises as physical transformation is portrayed as the primary key to gaining social acceptance. This study concludes that Imperfect not only reflects social realities concerning body and beauty but also invites viewers to critically evaluate how media constructs and reinforces burdensome beauty norms.